Polymorphisms in Toll-like receptors 2, 4, and 9 are highly associated with hearing loss in survivors of bacterial meningitis. - Gijs Th J van Well (Public Library of Science (PLoS), 2012)
Genetic variation in innate immune response genes contributes to inter-individual differences in disease manifestation and degree of complications upon infection. We recently described an association of single nucleotide polymorphisms (SNPs) in TLR9 with susceptibility to meningococcal meningitis (MM). In this study, we investigate the association of SNPs in multiple pathogen recognition and immune response genes with clinical features that determine severity and outcome (especially hearing loss) of childhood MM and pneumococcal meningitis (PM). Eleven SNPs in seven genes (TLR2, TLR4, TLR9, NOD1, NOD2, CASP1, and TRAIL) were genotyped in 393 survivors of childhood bacterial meningitis (BM) (327 MM patients and 66 PM patients). Genotype distributions of single SNPs and combination of SNPs were compared between thirteen clinical characteristics associated with severity of BM. After correction for multiple testing, TLR4+896 mutant alleles were highly associated with post-meningitis hearing loss, especially MM (p= 0.001, OR 4.0 for BM, p= 0.0004, OR 6.2 for MM). In a multigene analysis, combined carriership of the TLR2+2477 wild type (WT) with TLR4+896 mutant alleles increases the risk of hearing loss (p<0.0001, OR 5.7 in BM and p= 0.0001, OR 7.6 in MM). Carriage of one or both mutant alleles in TLR4+896 and TLR9 -1237 increases the risk for hearing loss (p = 0.0006, OR 4.1 in BM). SNPs in immune response genes contribute to differences in clinical severity and outcome of BM. The TLR system seems to play an important role in the immune response to BM and subsequent neuronal damage as well as in cochlear inflammation. Genetic markers may be used for identification of high-risk patients by creating prediction rules for post-meningitis hearing loss and other sequelae, and provide more insight in the complex immune response in the CNS possibly resulting in new therapeutic interventions.